1989
DOI: 10.1038/sc.1989.21
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support: a prophylaxis against stress bleeding after spinal cord injury

Abstract: SummaryThe incidence of upper gastrointestinal (UG /) bleeding and the effect of nutritional support was studied retrospectively in 166 spinal cord injured patients. Sixty six patients included in group 1 were started on oral diet when 'clinically ready' which resulted in a haphazard manner for provision of nutrition. One hundred patients in group 2 were treated according to an organised nutrition protocol. The protocol initiates total parental nutrition (TPN) If the patient is not tolerating an oral diet by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…An organized nutritional protocol (supplemental parenteral nutrition to meet defined energy requirements is initiated if not tolerating an enteral diet) significantly decreases the likelihood of upper GI bleeding, and allows patients to reach total energy requirements nearly threefold faster (Kuric et al, 1989). Although enteral feeding has historically been delayed in SCI patients secondary to concerns about ileus and other complications, studies have found that feeding these patients within the first 72 h is safe (Dvorak et al, 2004;Rowan et al, 2004) Discussion Unlike other trauma patients, such as those with traumatic brain injury, burns, or multi-trauma, patients with SCI do not demonstrate hypermetabolism following injury (Kearns et al, 1992;Kolpek et al, 1989;Rodriguez et al, 1991Rodriguez et al, , 1997.…”
Section: Resultsmentioning
confidence: 99%
“…An organized nutritional protocol (supplemental parenteral nutrition to meet defined energy requirements is initiated if not tolerating an enteral diet) significantly decreases the likelihood of upper GI bleeding, and allows patients to reach total energy requirements nearly threefold faster (Kuric et al, 1989). Although enteral feeding has historically been delayed in SCI patients secondary to concerns about ileus and other complications, studies have found that feeding these patients within the first 72 h is safe (Dvorak et al, 2004;Rowan et al, 2004) Discussion Unlike other trauma patients, such as those with traumatic brain injury, burns, or multi-trauma, patients with SCI do not demonstrate hypermetabolism following injury (Kearns et al, 1992;Kolpek et al, 1989;Rodriguez et al, 1991Rodriguez et al, , 1997.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study, published in 1989, examined 166 patients with spinal cord injury and suggests that there may be a time advantage to feeding patients. 45 The authors observed a statistically significant reduction in the incidence of GIB (7.6% to 2%) when the time to initiation of EN was reduced from 15.5 to 4.6 days. In a larger retrospective historical control study, Raff et al 46 demonstrated that EEN (within 12 hours posttrauma) was associated with a lower GIB rate than cimetidine or antacid therapy.…”
Section: Enteral Feeding and Gi Bleedmentioning
confidence: 91%
“…A prospective study, published in 1989, examined 166 patients with spinal cord injury and suggests that there may be a time advantage to feeding patients 45 . The authors observed a statistically significant reduction in the incidence of GIB (7.6% to 2%) when the time to initiation of EN was reduced from 15.5 to 4.6 days.…”
Section: Open Abdomenmentioning
confidence: 99%
“…A positive nitrogen balance develops after feeding, Neurocrit Care (2012) 16:184-193 189 resulting in a dilutional alkalinization from a gastric feeding tube and the reparative effects on the gastric mucosa that are possible explanations for this. Kuric et al [38] retrospectively demonstrated significantly lower incidence of GUD in patients with SCI when enteral nutrition was used. The combination of enteral nutrition and stress ulcer prophylaxis with ranitidine conferred significantly lower GI bleeding rates in blinded studies [77].…”
Section: Nutritionmentioning
confidence: 98%
“…Incidence of gastric ulcer disease (GUD) is commonly accentuated after SCI, ranging between 2 and 20% [35][36][37][38][39]. Further studies have postulated a multi-factorial causation [2, 38, and 40].…”
Section: Brain and Spinal Cord Injurymentioning
confidence: 99%